Desenvolvimento de um protótipo de sonda de intensidade sonora de baixo custo - Daniel Henrique Nunes Peixoto (2018)
Among the basic quantities of applied acoustic engineering, the sound intensity vector is the second most relevant, behind only root mean squared sound pressure, and is mainly used for identification and characterization of sound sources. The instruments capable of measuring this quantity are called sound intensity probes, whereas the ones of the pp type use two sound pressure transducers, installed very close to each other, to obtain the particle velocity using an finite-difference approximation to the spatial sound pressure gradient. This work presents the initial phase of the development of a low-cost p-p sound intensity probe, having as main motivation to contribute to the decrease of the dependence of commercial probes. The probe prototype was built with 3D printing aid and measuring equipment available at UFMG, namely: two preamplified microphones and a National Instruments acquisition board. MATLAB software was also used, in which it was implemented a signal processing capable of: i) calculating the sound intensity through the p-p method, ii) applying the phase-mismatch correction; iii) generate the responses of the performed experiments. Such experiments were designed with the intention of validating the developed probe prototype, based on relevant bibliographies. The experimental results proved to be quite consistent with the studied theory, thus allowing the validation of the signal processing algorithm developed for measurement of sound intensity with low cost. Finally, this research evidences the possibility of performing sound intensity measurements using the low-cost prototype and, more importantly, a base investigation on low cost probes has been produced which can be reproduced and improved freely.